(untitled) (Academic Journal of Internal Affairs, 2022)
The aim of the present study is to describe the possibilities inherent to the Modus Operandi Register, which are achievable by a symbiosis of the theoretical and practical approaches. The study presents the history of the Modus Oprandi registry, its operating principle, the forensic meaning of perseverance, and the range of data managed in the registry. It provides insight into the future of the electronic Modus Operandi Register through insight into forensic data collection at the police, which may include, for example, the application of artificial intelligence, research on perseverance, or the investigation of criminal life paths.